Prescribing safe supply: ethical considerations for clinicians - Duthie, Katherine (Journal of medical ethics, 2023)
The COVID-19 pandemic has exacerbated the drug poisoning epidemic in a number of ways: individuals use alone more often, there is decreased access to harm reduction services and there has been an increase in the toxicity of the unregulated drug supply. In response to the crisis, clinicians, policy makers and people who use drugs have been seeking ways to prevent the worst harms of unregulated opioid use. One prominent idea is safe supply. One form of safe supply enlists clinicians to prescribe opioids so that people have access to drugs of known composition and strength. In this paper, we assess the ethical case for clinicians providing this service. As we describe, there is much that is unknown about safe supply. However, given the seriousness of the overdose death epidemic and the current limited evidence for safe supply’s efficacy, we argue that it is ethically permissible for clinicians to begin prescribing opioids for some select patients.